PEMBUATAN BIOADITIF TRIACETIN DENGAN KATALIS PADAT SILICA ALUMINA - Aktawan, Agus; Mufrodi, Zahrul (Universitas Negeri Semarang, 2016)
Triasetin is a bioaditif to increase the octane number of the gasoline. Triasetin was generated from the reaction between giserol and acetic acid. Glycerol is a byproduct of biodiesel production. Triasetin production can reduce glycerol which is actually a waste by converting it into bioaditif having higher value. The reaction can be accelerated by addition of catalysts either solid or liquid catalyst. The reaction in this study used a solid catalyst types Silica Alumina. The reaction takes place in the three-neck flask reactor which is equipped with heating unit, mixers, and tools to take samples at regular intervals. Variables used in this research is the variety ofÂ reaction time and the reaction temperature (70, 80, 90, 100, and 1100C). The concentration of triasetin obtained will be known through the analysis of Gas Chromatography - Mass Spectrometry (GC-MS). The results of the analysis of GC or GC-MS treated or counted so getting glycerol conversion and selectivity of triasetin. The highest glycerol conversion 8,45% occurs at a temperature of 700C the reaction time of 90 minutes with triasetin selectivity 100%.